PEMAKNAAN RIBA DAN BUNGA BANK BAGI NASABAH BANK KONVENSIONAL DAN BANK SYARIAH - Agus Daniar (Communication, 2012)
The meaning of Riba for Muslim is very important because ti is forbidden by Islam Religion, however the different interpretation of Riba makes different perception of Bank Interest including among Muslim Scholars.  The purpose of this research is to uncover the meaning of Bank Interest and Riba by Muslim bank customers who are currently customer of Conventional and Sharia (Islamic) Bank The research uses qualitative approach with phenomenology perspective through in-depth interviews. All Informants are Muslim who have or are currently   customers of Conventional and Islamic Bank. Informants were selected by a purposive sampling method, located in Jakarta and Bandung. The results show that the informants interpret Riba negatively. Not all informants agreed that  Bank Interest is similar with  Riba, therefore there are   inconsistent informants who are  in one side, they agree  the Bank Interest is  Riba, but  they remains as  Conventional Bank customers for various reasons.